Clinical and Genetic Characteristics, Target Therapy Results in Children with Traps Syndrome (on Clinical Surveillance Data) - E. V. Antsiferova; T. V. Cherkashina; N. G. Wolf; I. Yu. Naumenko; E. A. Anikina; N. G. Kiseleva; N. Yu. Makarevskaya; T. E. Taranushenko; L. N. Antsiferova; E. Yu. Emelyanchik (Научно-практическая ревматология, 2021)
The complexity of diagnosing and predicting the course of TNF-receptor-associated periodic syndrome TRAPS determines the importance of studying the dependence of clinical manifestations on the variant of genetic mutation and the presence of modifier genes. We observed 5 children with an identified diagnosis of TRAPS. It was established that the disease onset in most cases is defined as a juvenile arthritis with systemic onset. Genetic variants with the replacement of cysteine residues are associated with an early debut and an aggressive course, the c.362G> A p.R121Q mutation is associated with an erosive damage to the spine. The case of a favorable course of TRAPS in siblings with a newly detected mutation is described. The development of urgent complications of TRAPS was revealed when basic therapy with canakinumab was canceled.